Lithium peroxide crystal clusters as a natural growth feature of discharge products in Li–O2 cells - Tatiana K. Zakharchenko; Anna Y. Kozmenkova; Daniil M. Itkis; Eugene A. Goodilin (Beilstein Journal of Nanotechnology, 2013)
The often observed and still unexplained phenomenon of the growth of lithium peroxide crystal clusters during the discharge of Li–O2 cells is likely to happen because of self-assembling Li2O2 platelets that nucleate homogeneously right after the intermediate formation of superoxide ions by a single-electron oxygen reduction reaction (ORR). This feature limits the rechargeability of Li–O2 cells, but at the same time it can be beneficial for both capacity improvement and gain in recharge rate if a proper liquid phase mediator can be found.